Biofuels global impact on renewable energy, production agriculture, and technological advancements - Tomes, Dwight; Lakshmanan; Songstad, David (Springer eBooks., 2011)
The biofuels area is one the most discussed research areas in biotechnology. This volume summarizes the current state of the art in the context of economic, agricultural productivity and sustainability as well as global perspectives. This volume is an excellent resource of diverse biofuels knowledge organized in sections and specific topics in an easily accessible and readable format. The broad scope of this book has application in the lab and classroom for the latest technological advances and also for entrepreneurs interested in the economic analysis and international scope of biofuels. Furthermore, the references within each chapter are a valuable resource for further study. Sections ? Historical perspective (David Songstad) and current research of the DOE Bioenergy Science Center (Russ Miller). ? Economics ? Competition between alternative uses for crop species (Greg Phillips) ? Economics of biofuels (Andy Aden) ? The feed stocks for biofuels (Jose Gonzalez-Hermandez), (Russel Jessup), (Katrin Jocob), (Maud Hinchee). ? The global perspective: Brazil (Paulo Arruda), India (Mambully Gopinathan) and China (Chun-Zhao Liu) ? Fermentation Technolgy ? Plant modification(Z.Y. Wang) ? Plant expressed enzymes (Manuel Sainz), ? Biorefineres and high-value co-products (W. Gibbons and S. Hughes), ? Biodiesel production (Bryan Moser). Chapters first published in: In Vitro Cellular & Developmental Biology - Plant Editor-in-Chief, Dwight T. Tomes Dwight Tomes is a Research Fellow in the Trait Discovery & Technologies group at Pioneer, a DuPont Company in Johnston, IA. My primary responsibilities since 1982 have been in transformation technology development in multiple crop species and trait development in several agronomic trait areas of corn. Dwight is currently the Editor-in-Chief of In-Vitro Plant. Prakash Lakshmanan, PhD, leads Molecular Breeding Program in David North Plant Research Centre, BSES Limited, Australia. His research focuses on crop improvement with particular emphasis on regulation of plant growth and resource use efficiency. Since 1998 he is working on sugarcane, a major industrial and biofuel crop. David Songstad is originally from South Dakota and attended South Dakota State University for his BS (Microbiology) and MS (Botany) and received his Ph.D. in Plant and Soil Science from the University of Tennessee. He has worked for the University of Illinois, Plant Biotechnology Institute (Canada), Pioneer Hi-Bred and Monsanto where he developed enabling technologies for corn tissue culture and corn transformation. He is currently the Global New Products Lead for Monsanto.